IMPROVING THE EFFICIENCY OF SECONDARY MARKET TRADING OF SHARES ISSUED BY JOINT-STOCK COMPANIES (American Journal of Interdisciplinary Research and Development, 2025)
The stock market plays a vital role in the economic development of any country, serving as an efficient mechanism for the redistribution of financial resources and the formation of investment capital. The shares issued by joint-stock companies are one of the primary instruments available on the stock market. Ensuring the efficient circulation of these shares in the secondary market is an essential factor in developing a robust, transparent, and attractive capital market infrastructure. The secondary market, which is a platform for the purchase and sale of previously issued securities, in particular shares, is critical for providing liquidity, determining fair value, and stimulating the issue of new shares. Therefore, improving the efficiency of secondary market trading of shares issued by joint-stock companies is one of the priority tasks of stock market development and the overall growth of the national economy.